The Implementation of Team Assisted Individualization Learning Model by Blended Learning in Vocational High School - Saputri, Winda Prasiska; Maryono, Dwi; Efendi, Agus (Universitas Sebelas Maret, 2020)
The emergence of the Covid-19 virus in Indonesia has caused in the learning process in schools to be changed into learning at home. The learning process is conducted by distance learning that makes use of technological developments. This study aims to determine the effect of the team assisted individualization (TAI) learning model by blended learning using Schoology on student learning results. This study uses a quantitative approach with a method of quasi-experimental design. Class X of Multimedia students in SMK Negeri 6 Surakarta were selected as the research sample. The experimental group was given a blended learning model using Schoology and team assisted individualization (TAI), and the control class was given a blended learning model using Schoology. The collected data in the form of learning test outcomes were used to find out the student cognitive ability, and observations were used to define the affective and psychomotor ability. The hypothesis t-test used independent-sample assessment with a 0.05 error level, showing the posttest learning results for both classes with a score of 0.002<0.05, which means that there are differences in learning outcomes between the two classes. Moreover, there was an improvement in student learning outcomes with the experiment class, gaining a total score of 0.3125, higher than 0.1354 of the control class.